Reference values for left and right ventricular trabeculation and non-compacted myocardium - André, Florian; Burger, Astrid; Loßnitzer, Dirk; Buß, Sebastian Johannes; Abdel-Aty, Hassan; Giannitsis, Evangelos; Steen, Henning; Katus, Hugo (International journal of cardiology, 2015)
Background - Since the differentiation between physiological and pathological trabeculation is challenging, we assessed its distribution in a reference population of selected healthy volunteers. - Methods - We studied 117 subjects (58 males) stratified into age tertiles and by gender. Cardiovascular magnetic resonance images were acquired using a standard SSFP-sequence. Left and right ventricular (LV/RV) end-diastolic (EDV), end-systolic (ESV) and trabeculated volumes indexed to the body surface area as well as ejection fraction (EF) were quantified in short-axis views. The maximum non-compacted-to-compacted (NC/C) ratio was measured in long-axis views. - Results - The trabeculated volumes were significantly larger in men than in women and decreased with age. The correlation between both was moderate (r=0.46; p<0.001). LV trabeculated volume was positively associated with EDV and ESV (r=0.74; r=0.59; both p<0.001) and negatively with EF (r=−0.27; p<0.005). It was no independent predictor for EF. The maximum NC/C ratio was >2.3 in 46.2% and >2.5 in 37.6% of the subjects, which is regarded as abnormal in current literature. The fraction of subjects with a maximum NC/C ratio >2.3 and the mean maximum NC/C ratio differed significantly between gender but not between age groups. An increasing NC/C ratio was associated with a significant decrease in EF (r=−0.21; p<0.05). - Conclusion - A considerable amount of healthy volunteers fulfils the current diagnostic criteria of LV noncompaction with female subjects showing a higher fraction of false-positive results than males. LV trabeculated volume is more pronounced in young subjects and declines with age. The use of age- and gender-specific reference values as provided in this study may facilitate the delineation of physiological and pathological findings.
Der Name Gianntisis ist falsch geschrieben
Gesehen am 23.07.2020